2019
DOI: 10.1093/icb/icz145
|View full text |Cite|
|
Sign up to set email alerts
|

Why do Large Animals Never Actuate Their Jumps with Latch-Mediated Springs? Because They can Jump Higher Without Them

Abstract: As animals get smaller, their ability to generate usable work from muscle contraction is decreased by the muscle’s force–velocity properties, thereby reducing their effective jump height. Very small animals use a spring-actuated system, which prevents velocity effects from reducing available energy. Since force–velocity properties reduce the usable work in even larger animals, why don’t larger animals use spring-actuated jumping systems as well? We will show that muscle length–tension properties limit spring-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 52 publications
3
62
0
Order By: Relevance
“…linear, massless, ideal springs), and that latches have infinite capacity for opposing spring loading, function as strict on-off switches, and can release (unlatch) instantaneously (Heitler, 1974;Roberts and Marsh, 2003). However, when springs and latches are parameterized more realistically to reflect the small size of many biological LaMSA systems, fundamental principles emerge, such as the mathematical delineation between systems best driven by a motor or muscle versus a spring and latch (Ilton et al, 2018;Sutton et al, 2019). Furthermore, changes in a system's output, such as takeoff velocity or launch duration, can be achieved by adjusting the relationships between the accelerated mass, motor or muscle behavior, and spring-latch dynamics (Ilton et al, 2018), which expands the capabilities of these systems well beyond previous idealized models of muscle, spring and latch systems (Galantis and Woledge, 2003).…”
Section: Lamsamentioning
confidence: 99%
“…linear, massless, ideal springs), and that latches have infinite capacity for opposing spring loading, function as strict on-off switches, and can release (unlatch) instantaneously (Heitler, 1974;Roberts and Marsh, 2003). However, when springs and latches are parameterized more realistically to reflect the small size of many biological LaMSA systems, fundamental principles emerge, such as the mathematical delineation between systems best driven by a motor or muscle versus a spring and latch (Ilton et al, 2018;Sutton et al, 2019). Furthermore, changes in a system's output, such as takeoff velocity or launch duration, can be achieved by adjusting the relationships between the accelerated mass, motor or muscle behavior, and spring-latch dynamics (Ilton et al, 2018), which expands the capabilities of these systems well beyond previous idealized models of muscle, spring and latch systems (Galantis and Woledge, 2003).…”
Section: Lamsamentioning
confidence: 99%
“…This higher reliance on elastic mechanisms at low versus high mass is generally consistent with our results. A subsequent study (Sutton et al, ) showed that in terms of maximizing jump height, the range of body mass in anurans spans the transition point where one mechanism becomes favoured over another. However, the mass at this transition point (2.5g) is almost an order of magnitude lower than the mass at which we see a majority of species whose jumping power is equivalent to muscle power (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…where species are less likely to amplify power; Figure ). Future studies could parameterize these models (Ilton et al, ; Sutton et al, ) with data on anuran muscle physiology to better understand the shift from elastic‐powered to muscle‐powered jumping with increased body mass.…”
Section: Discussionmentioning
confidence: 99%
“…How that energy is released and how that energy release interacts with synchronous muscle activation could also influence jump performance [5]. Because jumps are likely powered both by tendon recoil and muscle work [31,80], there may be a tradeoff between the work the muscle puts into tendon strain and that which is left available to power the jump during tendon recoil [100]. Future work could involve simulation of jumps in these subjectspecific models to assess the contributions of these dynamic factors.…”
Section: Limitationsmentioning
confidence: 99%